Infrastructure for commercial vehicle safety - Christopher M. Poe (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2017)
While there is increasing information on commercial motor vehicle (CMV) safety systems, truck automation, and truck platooning, there is less information on how roadway and infrastructure technology can improve truck safety, mobility, and efficiency using these technologies. Intelligent Transportation System (ITS), connected vehicle, and vehicle automation technologies are examined to identify safety and mobility applications that can leverage greater integration with infrastructure. Greater connectivity between commercial vehicles and the infrastructure has the potential to reduce crashes, increase productivity, and reduce fuel consumption and emissions. Connectivity holds immediate opportunity to expand traditional ITS solutions for safety and mobility by creating more effective applications that integrate infrastructure data directly with CMVs. This paper serves to facilitate the discussion on how the infrastructure can play a role in the technological advancements being made in the freight and CMV industry.
Keywords: 330; Lastkraftwagen; Verkehrssicherheit; Sicherheitstechnik; Intelligentes Verkehrssystem